Hartz IV: die Lösung für die Probleme in der Währungsunion? - Peter Bofinger (Wirtschaftsdienst, 2017)
Die Hartz-IV-Reformen werden immer wieder als deutsches Erfolgsmodell zur Senkung der Arbeitslosigkeit angeführt. Ist es daher sinnvoll, anderen Ländern der Währungsunion zu empfehlen, ähnliche Reformen durchzuführen? Peter Bofinger verneint das entschieden, da der Rückgang der Arbeitslosigkeit seit Mitte der 2000er Jahre in Deutschland weniger auf die Hartz-Reformen, sondern vielmehr auf die weitgehend überwundene Transformation nach der Wiedervereinigung zurückzuführen sei. – – The Hartz reforms are often regarded as the therapy which turned the so called 'sick man of Europe' into a global superstar. But this diagnosis was wrong. The strength of the German economy was overshadowed by the negative effects of reunification. The decline in unemployment can partly be attributed to the end of the transformation in East Germany. It also reflects the negative cyclical situation in 2005. This analysis is in line with the finding that compared e.g. with Italy and Greece, German unemployment assistance is still very generous. Thus, for the member states of the Eurozone Hartz IV is not a promising strategy. This could be different should wage moderation be cosnidered. However, if member states practice it simultaneously, this will lead to deflation. This calls for higher wage increases in Germany and a more symmetric adjustment.
Keywords: J2; J4; J5; 330